2021
DOI: 10.1021/acs.jpclett.1c01023
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Enhanced Visible-Light-Driven Photocatalytic Water Splitting on Novel Type-II GaSe/CN and Ga2SSe/CN vdW Heterostructures

Abstract: With the aggravation of environmental pollution and the energy crisis, it is particularly important to develop and design environment-friendly and efficient spontaneous enhanced visible-light-driven photocatalysts for water splitting. Herein novel type-II van der Waals (vdW) GaSe/CN and Ga 2 SSe/CN heterostructures are proposed through first-principles calculations. Their electronic properties and photocatalytic performance are theoretically analyzed. In particular, their appropriate band gap and band-edge pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(37 citation statements)
references
References 77 publications
1
36
0
Order By: Relevance
“…Zhang et al reported the enhanced stability of GaSe/CN and Ga 2 SSe/CN heterostructures by considering vdW interaction. 46 Li et al…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al reported the enhanced stability of GaSe/CN and Ga 2 SSe/CN heterostructures by considering vdW interaction. 46 Li et al…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The application of vdW potential plays a major role in maintaining the stability of bilayer systems. Zhang et al reported the enhanced stability of GaSe/CN and Ga 2 SSe/CN heterostructures by considering vdW interaction . Li et al have also reported that the carbon nanomaterial acts as an effective anchor in Li–S ions batteries employing vdW .…”
Section: Results and Discussionmentioning
confidence: 99%
“…conversion efficiency of several 2D structures. 27,59,60 The details involving the formula, the overpotential of CBM and VBM, the difference between the vacuum energy levels relative to the two surfaces, and the obtained Z are presented in the ESI. † As shown in Fig.…”
Section: The Solar-energy-to-hydrogen Conversion Efficiency and The P...mentioning
confidence: 99%
“…6(b), by using the formulas w Ga2SeS = E vac À E SC C and IP Ga2SeS = E vac À E SC V , respectively. 70 The carrier mobility is a parameter that is essential for efficiency in electronic, 71-73 photovoltaic 74,75 and photocatalytic [76][77][78] applications. However, most semiconductors have low carrier mobilities, 79 which restrict their feasibility in nano-electronic applications.…”
Section: A Structural Analysis and Electronic Properties Of The Prist...mentioning
confidence: 99%